2017
DOI: 10.1136/tobaccocontrol-2017-053891
|View full text |Cite|
|
Sign up to set email alerts
|

Tobacco industry strategies undermine government tax policy: evidence from commercial data

Abstract: ObjectiveTaxation equitably reduces smoking, the leading cause of health inequalities. The tobacco industry (TI) can, however, undermine the public health gains realised from tobacco taxation through its pricing strategies. This study aims to examine contemporary TI pricing strategies in the UK and implications for tobacco tax policy.DesignReview of commercial literature and longitudinal analysis of tobacco sales and price data.SettingA high-income country with comprehensive tobacco control policies and high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
153
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(164 citation statements)
references
References 48 publications
8
153
1
2
Order By: Relevance
“…The observed practice of reducing tobacco weights by about 2% per year will have offset, to some extent, any annual tax increases designed to make tobacco less affordable. In the UK for instance, annual tax increases on RYO have been about 2% above inflation since March 2009, with significantly bigger increases only taking place in March 2011 and 2012 (Hiscock et al, 2017). This implies the action of smokers has ensured that the real cost of smoking a RYO cigarette will not have changed significantly during this time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed practice of reducing tobacco weights by about 2% per year will have offset, to some extent, any annual tax increases designed to make tobacco less affordable. In the UK for instance, annual tax increases on RYO have been about 2% above inflation since March 2009, with significantly bigger increases only taking place in March 2011 and 2012 (Hiscock et al, 2017). This implies the action of smokers has ensured that the real cost of smoking a RYO cigarette will not have changed significantly during this time.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that the tobacco industry is now segmenting RYO alongside FM cigarettes(Hiscock et al, 2017), which simultaneously allows them to maximise profits with more expensive brands and offer affordable tobacco to the most price conscience smokers. This also allows them to vary the extent to which they pass on higher tobacco duty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some jurisdictions also mandate minimum pack quantities for other tobacco products, such as cigars and cigarillos (eg, Canada, Singapore, and New York City). These policies are sometimes combined with minimum price regulations to ensure that larger pack sizes command a consistently higher retail price and are not offset, for example, by tobacco company price discounts 2. The goal of minimum pack quantity regulations is to reduce the availability of cheap tobacco to youth and other price-sensitive consumers.…”
mentioning
confidence: 99%
“…As Hiscock and colleagues demonstrate in this issue,2 even when tobacco taxes are increased regularly, tobacco companies cleverly undermine them using a variety of strategies. These include introducing cheaper products, changes in pack sizes, price-marking and undershifting, where companies absorb at least temporarily the difference in price so that consumers experience little to no change when taxes increase (and thus are less likely to try to quit as a result of the tax increase).…”
mentioning
confidence: 99%